Cover Image. (26th January 2021) - Luks, Francois I.; Collins, Scott; Xia, Jimmy; Cao, Shiliang Alice; Rios, Matthew
Abstract : The cover image is based on the Original Article Combination of volume‐rendering 3D surface modeling and medical illustration to capture the living fetus by Francois I. Luks et al., https://doi.org/10.1002/pd.5844 .